Exploring the Diverse Range of Bee Pollinators Associated with the Medicinal Plant Vitex negundo (Lamiaceae) in West Bengal, India - Riju Nath; Samrat Saha; Sudipta Dey; Bhaswati Majumder; Sayan Sardar; Pousabh Das; Rameshkumar A (Sociobiology)
Chinese chaste tree, Vitex negundo L., (family Lamiaceae) is an important medicinal plant. The present study focused on the floral morphology and the diversity of bees pollinating its flowers in three different geographical regions of West Bengal, identifying 56 species from 20 genera across four families of Apoidea.